2010
DOI: 10.1590/s1984-82502010000200003
|View full text |Cite
|
Sign up to set email alerts
|

Development of a dissolution test for lamotrigine in tablet form using an ultraviolet method

Abstract: A dissolution test for tablets containing 100 mg of lamotrigine was developed and validated. The dissolution test was applied to compare the dissolution profile of Neural ® with the reference product Lamictal ® . The analysis procedure was carried out using a simple ultraviolet method at 267 nm. After the determination of solubility and sink conditions, the parameters selected were paddles at 50 rpm, 900 mL of 0.01 M hydrochloric acid, and 30 minutes duration (single point). This method was validated for speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
3
4
0
1
Order By: Relevance
“…The initial dissolution profiles revealed that coamorphization caused a pronounced increase in the dissolution rate in all of the systems. The concentration in solution appeared to level off; i.e., the systems attained equilibrium, in about 2 h. The aqueous solubility of the crystalline LAM, in phosphate buffered saline (pH 6.8; 37 °C), was reported to be ∼394 and 382 μg/mL. , This is in excellent agreement with the “equilibrium” concentration (Figure a). In the coamorphous system, the concentration in solution was approximately doubled.…”
Section: Resultssupporting
confidence: 66%
“…The initial dissolution profiles revealed that coamorphization caused a pronounced increase in the dissolution rate in all of the systems. The concentration in solution appeared to level off; i.e., the systems attained equilibrium, in about 2 h. The aqueous solubility of the crystalline LAM, in phosphate buffered saline (pH 6.8; 37 °C), was reported to be ∼394 and 382 μg/mL. , This is in excellent agreement with the “equilibrium” concentration (Figure a). In the coamorphous system, the concentration in solution was approximately doubled.…”
Section: Resultssupporting
confidence: 66%
“…The content of LMT in tablets and in dissolution samples was determined by measuring the absorbance using UV/Vis spectrophotometric method, which was previously published and confirmed [ 19 , 20 ]. The absorbance of LMT was measured at a wavelength of 267 nm in pH 1.2 dissolution medium [ 19 ] and 304 nm in pH 6.8 dissolution medium [ 20 ].…”
Section: Methodsmentioning
confidence: 85%
“…Any change requires an evaluation of the method's performance. The validation of the method, comparative tests with standard methods, and co-validation between laboratories are the possible strategies to achieve this goal [18]. In this case, the method was validated in terms of the linearity, precision, repeatability, measurement of uncertainty, and accuracy.…”
Section: Discussionmentioning
confidence: 99%